Variability in the polar vortex and its interaction with the climate system - Dimdore-Miles, OB (2021)
Variability in the strength of the Northern Hemisphere stratospheric polar vortex is an important climate feature. Strong vortex conditions, as well as disruptions of the vortex, known as sudden stratospheric warmings (SSW), are associated with significant tropospheric and surface variations. This makes them an important feature for improving the skill of seasonal weather forecasts. This thesis addresses some ongoing research questions regarding the nature of variations in the polar vortex and their interactions with the wider climate system.